Analysis of the Tooth Surface Modeling and Honing Characteristic of Internal Gear Honing Stone based on Matlab - Han Jiang; Zhao Feihu; Zhang Kuibang; Xia Lian (Jixie chuandong)
Based on the processing principle analysis of internal gear honing,the space coordinates system of honing stone and workpiece are built and the contact line equation of workpiece and the tooth surface equation of honing stone are derived by the contact condition of conjugate surfaces to build more accurate tooth surface model of honing stone. The 3D model of honing stone and its tooth surface model are built in Solid Works by using the datum of contact lines from being calculated in Matlab with parametric programs. The influence analysis about variable shaft angle dressing method on gear tooth surface are carried out by using relative velocity on contact points and honing path on gear tooth surface.